Pelaksanaan Problem Based Learning (PBL) pada Pelajaran Pendidikan Agama Islam di SMA Negeri 9 Mukomuko - Meriska, Ega; Muliati, Indah (Lembaga Yasin AlSys, 2023)
This study aims to find out how the implementation of Problem Based Learning (PBL) in Islamic Religious Education lessons at SMAN 9 Mukomuko. The subjects of this study were students of class X IPS at SMAN 9 Mukomuko, and the informants of this study were teachers of Islamic Religious Education at SMAN 9 Mukomuko. The method chosen in this study is a qualitative method with a descriptive approach. The results of this study are that in implementing teacher learning using 5 syntax or Problem Based Learning (PBL) steps, namely student orientation, identifying and organizing students, guiding individual and group investigations, developing and preparing works, and analyzing and evaluating processes. solution to problem. The teacher prepares a learning implementation plan (RPP) at each meeting and learning media, textbooks, Al-Qur'an, internet, and other references.